Inhibition of advanced glycation end product formation and serum protein infiltration in bioprosthetic heart valve leaflets: Investigations of anti-glycation agents and anticalcification interactions with ethanol pretreatment. (October 2022) - Zakharchenko, Andrey; Rock, Christopher A.; Thomas, Tina E.; Keeney, Samuel; Hall, Emily J.; Takano, Hajime; Krieger, Abba M.; Ferrari, Giovanni; Levy, Robert J.
Abstract: Bioprosthetic heart valves (BHV) fabricated from heterograft tissue, such as glutaraldehyde pretreated bovine pericardium (BP), are the most frequently used heart valve replacements. BHV durability is limited by structural valve degeneration (SVD), mechanistically associated with calcification, advanced glycation end products (AGE), and serum protein infiltration. We investigated the hypothesis that anti-AGE agents, Aminoguanidine, Pyridoxamine [PYR], and N-Acetylcysteine could mitigate AGE-serum protein SVD mechanisms in vitro and in vivo, and that these agents could mitigate calcification or demonstrate anti-calcification interactions with BP pretreatment with ethanol. In vitro, each of these agents significantly inhibited AGE-serum protein infiltration in BP. However, in 28-day rat subdermal BP implants only orally administered PYR demonstrated significant inhibition of AGE and serum protein uptake. Furthermore, BP PYR preincubation of BP mitigated AGE-serum protein SVD mechanisms in vitro, and demonstrated mitigation of both AGE-serum protein uptake and reduced calcification in vivo in 28-day rat subdermal BP explants. Inhibition of BP calcification as well as inhibition of AGE-serum protein infiltration was observed in 28-day rat subdermal BP explants pretreated with ethanol followed by PYR preincubation. In conclusion, AGE-serum protein and calcification SVD pathophysiology are significantly mitigated by both PYR oral therapy and PYR and ethanol pretreatment of BP.